Diferentes aspectos da fecundidade do sêmen de jumentos e da gestação de éguas submetidas à cruzamentos inter-espécie - Alice Teixeira Gonczarowska (2011)
The main objective of the present dissertation was to study different aspects of pregnancy in mares subject to interespecific matings (mare x jackass), for that purpose, a)to follow the development of pregnancy during the mule embrionary period (40 days), using the measure of the embrionary vesicles through ultrassonography (Experiment I); b)to determine the actual time span of the mules pregnancy (Experiment II); c)to assess the ratio between sex products from mares bred to a jackass (Experiment II); d)to compare the effect of three semen extenders, being one milk based and the other two egg yolk based (Experiments II and III) on mare´s fertility, when inseminated with fresh or cooled jackass semen; e)to study the reproductive efficiency and the rates of pregnancy loss in mares bred to horses or jackasses by monitoring females for a minimal period of 128 days reaching the maximun of 205 days (Experiment III and IV); f)to monitor the interespecific pregnancies until labor, to determine the percentage of pregnancy losses from the tenth day to delivey (Experiment II); g)to evaluate the jackass influence, the reproductive category of the mare, the mares age and month of conception on the reproductive efficiency, including the embryonic and fetal losses (Experiment II). For this, five experiments were performed in the 2007/2008 and 2010/2011 breeding seasons in Lagoa Dourada, Minas Gerais. At experiment I 167 vesicles of mules embryos were measured, obtaining a growth curve from 10 to 37 days of pregnancy (R2=0.6875), represented by the regression equation: Pregnancy (days) = (0.1876 x height) + (0.3780 x width) + 5.3713. At experiment II were evaluated two extenders based on skim milk-glucose (T1) or egg yolk-glycine (T2) about mares fertility inseminated with fresh (EIIa) or cooled semen at 5°C stored for 12 hours (EIIb) for which collection of total semen of five Pêga jackasses. In EIIa and EIIb, 67 and 141 mares were used, respectively, without a breed definition, being uniformly distributed in two groups. The mares were inseminated every Tuesday, Thursday and Saturday, once they presented one follicle of 3.0 to 3.5 cm of diameter until ovulation. Pregnancy was detected through rectal palpation, a regular use of teasers and ultrassonography made on a regular intervals of 14 days. The conception rates, length of gestation and sex of the products did not differ (p<0.05) between the treatments. The rates of pregnancy loss were influenced (p<0,05) by the treatments, and the average was 33.09%. At experiment III, the sperm rich semen fraction was diluted in skim milk-glucose (SMG) (T1) or egg yolk-lactose (EYL) (T2) , cooled at 5°C using 22 mL as a total dose (EIIIa) or in two different concentrations (T3- 400 x 106; T4- 800 x 106) (EIIIb) in the same extender (SMG). Fertility was evaluated using 44 (EIIIa) and 59 (EIIIb) mares inseminated with stored semen for 12 to 24 hours. The mares were inseminated every Monday, Wednesday and Friday, since they had one follicle of 3.0 to 3.5 cm of diameter until the ovulation. The pregnancy was detected using rectal ultrassonography at least 12 days from ovulation. The conception rates using SMG doses were higher (p<0.05) (56.52% - T1; 41.46% - T3; 47.37% - T4) than the one got from the use of EYL (T2 - 4.76%). At experiment IV, 59 mares were used, impregnated with donkey (T1) or horse (T2) semen by natural breeding, since they had one follicle of 3.0 to 3.5 cm of diameter, every 48 hours, until the ovulation. The conception rates did not differ (p<0.05) between the treatments, although the rates of pregnancy loss were higher (28.57%) in mares bred to horses than for mares bred to jackasses (7.14%). The data of the experiments II, III e IV were grouped to perform a meta-analysis and evaluate the features of pregnancies of mares subject to interespecific matings. The reproductive category, conception rates and pregnancy loss rates did not differ (p<0.05) between mares bred to horses or jackasses. However, in the group of mares subject to interespecific matings, was observed (p<0.05) effect of the month and bimester of conception on pregnancy loss rates, that were higher (p<0.05) in January, February and March (35.71%, 47.62% e 50%) and in the bimester February/March (47.92%). The reduction of the LH secretion patterns, in the end of the breeding season, could respond for the greatest rates of pregnancy loss in mares conceiving at its end, mainly during February/march.